Tanjung Piandang: a journey back to my hometown's heart / Fadhlina Mahat … [et al.] - Mahat, Fadhlina; Abdul Hadi, Arnieyantie; Ab Rahman, Rabiatul Adawiyah; Ahmad, Johanna Adlin (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Tanjung Piandang, a serene town nestled within the district of Parit Buntar, Perak, is more than just a place on a map-it holds a special place in my heart. While I didn't grow up here, it's where I was born, and it remains my refuge when I 'balik kampung' for family gatherings, Raya celebrations, and 'kenduri' events. This town's charm lies in its beautiful blend of tradition, nature, and steady development, representing a harmonious coexistence that draws me back every time. My connection with this town grew stronger when I began my career here after completing my diploma. I got my first job with the Kerian District Council (MDK), marking the start of my journey toward financial independence. Working in this environment gave me a deeper appreciation for the people and the place, as I witnessed the development of Parit Buntar firsthand. What once was a quiet town is now home to a thriving community, with local markets, eateries, and new businesses shaping the landscape.